Literature and Media After 1989 - Hopfinger, Maryla (Cross-Roads, 2020)
This book discusses the direction of changes in contemporary culture at the turn of the 20th and 21st centuries in Poland on the example of mutual relationships between literature and the media, such as film, radio, TV and the Internet. The interdisciplinary approach adopted by the author combines literary and media studies with the perspectives of social communication, anthropology and sociology of culture. The book focuses on topics such as reconfiguration of culture, expansion of the media, situation of literature and the central place of audio-visual parallels (auteur film, TV series, PC games). The author notes that both literature and the media are situated between art and communication today and both share the meta-cultural role of natural languages.